Oral microbiocenosis state under different approaches of replacing dental crown defects - Ye.A. Sardykov; O.V. Ishchenko; O.O. Fastovets (Medičnì Perspektivi)
Dental caries is one of the most common health problems. The aim of the research was to study the spectrum of microbiota, which is part of the dental biofilm, and its biological properties. The study involved 90 participants of the study group and 20 of the control group. Dental plaque and saliva were used as principal clinical specimens. The main research method was bacteriological. All samples from study participants were positive for microbiota. At the initial collection of material, 395 unique isolates were obtained: 338 from patients with caries and 57 from healthy volunteers. The microbiocenosis of the oral cavity associated with the development of caries contained such eudodominants as Streptococcus mutans, Peptostreptococcus spp., Fusobacterium spp., Prevotella spp. and dominants Streptococcus pyogenes, Enterobacterales, Prevotella spp. and Candida albicans. In contrast the eudominants of the healthy oral cavity were microorganisms with known commensal properties, in particular Streptococcus salivarius, Aerococcus viridans, Veillonella spp. After the dental treatment, significant shifts in the taxonomic composition of the dental biofilm were observed. Therefore, the composition of the oral cavity microbiocenosis in participants who underwent restoration of the dental crown defects with zirconium inserts approached patients to the healthy cohort participants. The eudodominants of the oral microbiocenosis of the participants who underwent direct restoration were S. mitis, Peptostreptococcus spp. and Veillonella spp. In zirconium restoration, the commensals S. salivarius and A. viridans were eudodominants. The obtained isolates of opportunists possessed high virulence properties. Streptococcus spp. cultures were sensitive to norfloxacin screening in only 28.6% of cases. Among cultures of the genus Staphylococcus, 23.8% were methicillin resistant. Representatives of Enterobacterales had chemotherapeutic sensitivity that varied significantly depending on the group of antimicrobial agents. Using disks with phenylboronic acid, ethylenediaminetetraacetic acid and cloxacillin, it was established that Klebsiella spp. were producers of class A carbapenemases (n=3) and contained AmpC (n=3). Carbapenemases were also produced by at least 65.2% of the studied cultures of non-fermenting gram-negative microorganisms. In our study, all obtained isolates were also endowed with the ability to form a biofilm. Therefore, microbiological research in dentistry should be considered as one of the objective methods for assessment of health of the oral cavity and will also have advantages in choosing a method of correcting defects of dental crown parts and in some cases, making an informed decision about the prescription of antimicrobial treatment.